2005
DOI: 10.1016/s1726-4901(09)70242-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Single-Agent Gemcitabine Chemotherapy in Patients with Non-Small-Cell Lung Cancer in Whom Previous Chemotherapy Has Failed

Abstract: Salvage, single-agent chemotherapy with gemcitabine has modest activity, is well tolerated, and yields good survival in NSCLC patients who have failed previous chemotherapy. Such single-agent therapy may therefore be suggested for use in patients with good performance status who ask for further chemotherapy, when disease progresses after cisplatin-based therapy, but especially after second-line docetaxel therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The response rate of phase II single-agent gemcitabine in second-line NSCLC treatment has ranged from 0 to 20.6%, and median survival from 4 to 7.9 months [9][10][11][12]. The present study, combining gemcitabine with UFUR, demonstrated a response rate of 15.6% and a median survival of 13.2 months, which was within or better than the ranges of single-agent gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The response rate of phase II single-agent gemcitabine in second-line NSCLC treatment has ranged from 0 to 20.6%, and median survival from 4 to 7.9 months [9][10][11][12]. The present study, combining gemcitabine with UFUR, demonstrated a response rate of 15.6% and a median survival of 13.2 months, which was within or better than the ranges of single-agent gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, gemcitabine is safe and easy to administer in an outpatient setting. Gemcitabine may have activity in the second-line treatment of NSCLC, with a single-drug response rate ranging from 0 to 20.6% reported in phase II studies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…From September 1998 to October 2005, 461 patients with NSCLC entered nine clinical trials, 7-15 which included treatment with docetaxel alone (weekly or triweekly schedules, n ϭ 185) 9,11 or combined with other agents (with ifosfamide, n ϭ 50; with gemcitabine, n ϭ 36; and with tegafur ϩ uracil, n ϭ 24), 9,13,14 gemcitabine alone (n ϭ 20) or combined with other agents (with tegafur ϩ uracil, n ϭ 45 and with vinorelbine, n ϭ 17), 7,8,15 and gefitinib alone (n ϭ 63) or with vinorelbine (n ϭ 21). 10,12 Their data had been reviewed and updated.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] We wanted to find out whether there existed differences in tolerance and efficacy between young and old patients receiving salvage chemotherapy or salvage targeted therapy with EGFR-TKI. [7][8][9][10][11][12][13][14][15] We wanted to find out whether there existed differences in tolerance and efficacy between young and old patients receiving salvage chemotherapy or salvage targeted therapy with EGFR-TKI.…”
mentioning
confidence: 99%
“…Informed consent was signed by all patients. The seven trials included a single-agent gemcitabine study (20 patients), 8 a vinorelbine plus cisplatin study (22 patients), 9 a vinorelbine plus gemcitabine study (17 patients), 10 a docetaxel plus gemcitabine study (36 patients), 11 a docetaxel plus ifosfamide study (50 patients), 12 a docetaxel with three different schedules study (161 patients), 13 and a single-agent gefitinib study (36 patients). 14 The clinical characteristics, response rate, toxicity profiles, and survival were compared between the different treatment regimens.…”
Section: Methodsmentioning
confidence: 99%